Hydrogen evolution on single-crystal copper and silver: A theoretical study - Santos, Elizabeth del Carmen (2010)
Hydrogen evolution on single-crystal copper and silver is investigated by a combination of density functional theory and a theory developed in our own group. At short times, the reaction rate is determined by the transfer of the first proton to the electrode surface. In accord with experiment, we find for both metals that this reaction proceeds faster on the (111) surfaces than on the (100) ones. The main cause is the lower, that is, more favourable, adsorption energy on the former surfaces. On both silver surfaces, the second step is electrochemical desorption. The same mechanism is likely to operate on copper.